Pencarian Rute Terpendek menggunakan Algoritma Genetika (Studi Kasus : Pengoptimalan Mobilitas Kota Salatiga Terhadap Kota-Kota Tetangga) - Isai, Agustho; Nugroho, Adi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The increase in population in an area has a significant impact on vehicle density in that area. The problem that often arises is traffic jams that occur on several routes at once. This factor is a common problem, which is quite disturbing to the public and road users. To overcome this problem, the genetic algorithm method is used as a solution method. This case study was set at the regional or city level around Salatiga City, including Ambarawa City, Semarang City, Boyolali City, Solo City and Magelang City. By using the genetic algorithm method, the fastest route with the shortest distance can be found. The Genetic Algorithm used in this research allows optimal shortest route search results. Apart from that, this research can also minimize the distance and travel time of several alternative routes obtained, thus providing significant benefits in developing the transportation system in the region.